Desenvolvimento de produto estruturado à base de tucupi e suas aplicações gastronômicas - Amaral, Cássia Santos do (2024)
Tucupi, an ingredient strongly present in the food culture of Pará, has been the subject of comprehensive studies covering anthropological, cultural, and physical-chemical aspects. In gastronomy, its diverse use, especially in sauces and broths, stands out in typical dishes from the northern region of Brazil. This work aims at innovation and development, focusing on elaborating and characterizing a structured product based on tucupi using hydrocolloids. The objective is to enable improvements in the transport and use of this food and expand the study perspectives of tucupi. Commercial tucupi was freeze-dried to obtain the structured ones and resuspended in distilled water at a proportion of 0.1 g/mL. The hydrocolloids added were k-carrageenan, i-carrageenan, and konjac, all at a concentration of 1%. After preliminary tests, four different formulations were reached: Kappa 50% - Iota 50%, Kappa 75% - Iota 25%, Kappa 50% - Konjac 50% and Kappa 75% - Iota 25%. Physicochemical analyses, color parameters, antioxidant capacity, phenolic compounds, rheological study, and sensory evaluation were carried out through a focus group. The combinations of hydrocolloids used in this study did not influence the physicochemical characteristics, color, antioxidant capacity, and phenolic compounds. Samples of commercial and resuspended tucupi presented values within the standards established by current legislation, with variations that can be attributed to the lack of standardization, indeterminate manipueira fermentation time, and the great variety of cassava used to obtain tucupi. The value obtained through pH analysis for the commercial tucupi sample was 4.32 (± 0.01) and, for resuspended tucupi, 4.60 (± 0.01). The pH of the structured products varied between 4.16 (± 0.01) and 4.21 (± 0.01). For acidity (g of lactic acid/100 mL), the value for the commercial tucupi sample was 0.21 (± 0.01) and, for resuspended tucupi, 0.13 (± 0.01). The acidity of structured products varied between 0.19 (± 0.01) and 0.22 (± 0.01). The analysis of soluble solids (oBrix) of commercial tucupi showed 6.83 (± 0.06), while the resuspended value was 9.20 (± 0.00). The values obtained in the water activity analysis (Aa) were 0.98 (± 0.01) for commercial tucupi and 0.97 (± 0.01) for resuspended tucupi. All structured product formulations had the same Aa value (0.97 ± 0.01). In the color evaluation, the commercial tucupi sample presented a value of 46.893 (± 0.74) for L*, 3.013 (± 0.07) for a*, 24.683 (± 0.74) for b*, 24.870A (± 0.74) for C* and 83.043 (± 0.06) for h*. The resuspended tucupi sample presented a value of 45.047 (± 0.08) for L*, 5.480 (± 0.02) for a*, 34.077 (± 0.04) for b*, 34.510B (± 0.03) for C* and 80.863A (±0.04) for h*. For structured ones, color analysis values varied between 42.05 (± 0.44) and 42.743 (± 0.16) for L*, 6.030 (± 0.12) and 6.293 (± 0.31) for a*, 28.943 (± 1.24) and 30.947 (± 0.19) for b*, 29.593 (±1.27) and 31.580 (±0.24) for C* and 77.870 (± 0.12) and 78.870a (± 0.81) for h*. The analysis of phenolic compounds in commercial tucupi resulted in a value of 60.50 (±2.09) GAE/100 mg, the antioxidant capacity ABTS●+ 3.80 (±0.23) μM Trolox/g of pulp. The phenolic compounds of resuspended tucupi resulted in a value of 95.50 (±5.04) GAE/100 mg and the antioxidant capacity ABTS●+ 3.19 (± 0.20) μM Trolox/g of pulp. The phenolic compounds of the structured ones varied between 91.14 (± 2.14) and 96.54 (±3.14) GAE/100 mg, and the ABTS●+ antioxidant capacity, between 2.30 (±0.02) and 3.09 (± 0.15) μM Trolox/g pulp). The temperature scan was carried out in the rheology analysis of the structures, and no transitions were observed during the investigated temperature phase (90 to 20 °C). Quantifying phenolic compounds and antioxidant capacity in tucupi and its compounds is very important, as results are scarce in the literature. In the sensory evaluation, the two formulations of k-carrageenan and i-carrageenan were preferred. Three culinary preparations using structured products were developed using the structured product: shrimp risotto, chicken thighs with roasted vegetables, and grilled cheese with sugarcane molasses. The feasibility of developing a structured product based on tucupi and its gastronomic applications was verified.